Public understanding on geoconservation strategies at the Passagem das Pedras Geosite, Paraíba (Brazil): contribution to the Rio do Peixe Geopark Proposal - Santos, Wellington Francisco Sá dos (2019)
The Rio do Peixe basin, which is developed during the Lower Cretaceous, consists of the Sousa, Uiraúna-Brejo das Freiras, Pombal and Vertentes sub-basins. They have abundant ichnofauna represented by dinosaur tracks of theropods, sauropods and ornithopods, these being the main objects of geological heritage in the region. The majority of palaeontological sites are found in the Sousa basin and the most important geosite in terms of distribution of fossil footprints is Passagem das Pedras (Municipality of Sousa—Sousa basin). In 1992, this area was classified as the BValley of the Dinosaurs Natural Monument^ and initially had high-quality infrastructure and trained tour guides; however, following a period of neglect, the local infrastructure became precarious. In 2014, revitalization of the museum, kiosks and walkways in Valley was performed; however, there are inefficient measures to protect the dinosaur footprints from human and natural threats. Thus, 500 interviews with the urban and rural population of Sousa in addition to traders and teachers were done, seeking public understanding of geoconservation strategies at the Passagem das Pedras geosite. Critical analysis of the results was performed as a contribution to the proposal for the Rio do Peixe Geopark. The perception is that the geoconservation strategies are not effective in protecting the Passagem das Pedras geosite or in raising the Sousa population’s awareness as to the importance of geological heritage. The other palaeontological sites of the Sousa basin are also quite vulnerable and with deteriorating geological elements. Therefore, the region currently has low potential to become a geopark.